Patient participation in clinical encounters: a systematic review to identify self‐report measures. (11th March 2014) - Mavis, Brian; Holmes Rovner, Margaret; Jorgenson, Sarah; Coffey, John; Anand, Nandita; Bulica, Emi; Gaulden, Carolyn Marie; Peacock, Jacob; Ernst, Alycia
Abstract: Background: There is evidence suggesting that active participation of patients in their health care can improve the quality of care and decrease health‐care costs. Further, patient reports of their health‐care experience are increasingly used to monitor health‐care quality. Objective: This paper describes a systematic review of peer‐reviewed studies to identify measures of patients' active participation in their encounters with health‐care providers. Methods: A systematic literature review was conducted for publications indexed from 1975 to 2011. Of interest were self‐reported measures of patient participation that were not limited to a specific health concern. All abstracts were reviewed independently by two authors, and the full paper was considered for those meeting inclusion criteria. Main Results: From a review of 4528 citations, ten measures were identified. The approaches to development of the measures varied considerably, as did their study samples and their psychometric quality. Discussion: These measures represented three conceptual frameworks: empowerment and self‐efficacy, therapeutic alliance, and consumerism/satisfaction. They provide a more comprehensive perspective of patients' experiences of their provider encounters, and a better understanding patient behaviour enhanced the quality of health‐care delivery or improved health outcomes. These measures underscore the continuing challenge of defining patient participation and the multiple theoretical approaches that underlie this form of patient behaviour. Conclusions: Current interest in quality‐related physician report cards gives significant weight to patients' self‐reported experiences as one dimension of physician performance. It is critical to identify the specific focus and quality of measures selected for this and research purposes.